Knowledge, Attitude, and Purchase of Life Insurance Among the Faculty Members of a State University - Capricho, Raul A; Paradero, Angelita L; Casinillo, Leomarich F (Indonesian Journal of Social Research (IJSR), 2021)
Life insurance companies in the Philippines are active contributors to the country’s social and national development. This study aimed to assess the purchase of life insurance among the faculty members of the Visayas State University-Main Campus in Baybay City, Leyte, Philippines. A stratified random sampling procedure was used to gather pertinent data from 195 participants. Descriptive measures, correlation analysis, and binary logit regression analysis were used to examine the socio-demographic data and the level of knowledge and attitude in regards to the faculties’ decision to purchase life insurance. Results showed that educational attainment and knowledge on life insurance significantly influence the purchase of life insurance. Furthermore, purchase on life insurance increases as the faculty becomes more knowledgeable about the benefits of having life insurance coverage. Hence, life insurance companies should conduct a thorough orientation in view to their procedure, policy, and benefits to increase their purchase.